Stochastic Jumping Robots for Large‐Scale Environmental Sensing. (18th February 2022) - Hird, Julian; Conn, Andrew T.; Hauert, Sabine
Abstract : Single‐use jumping robots that are mass‐producible and biodegradable could be quickly released for environmental sensing applications. Such robots would be pre‐loaded to perform a set number of jumps, in random directions and with random distances, removing the need for onboard energy and computation. Stochastic jumpers build on embodied randomness and large‐scale deployments to perform useful work. This paper introduces simulation results showing how to construct a large group of stochastic jumpers to perform environmental sensing, and the first demonstration of robot prototypes that can perform a set number of sequential jumps, have full‐body sensing, and are well suited to be made biodegradable. An interactive preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.163525369.97561426 . Abstract : Stochastically jumping, mass‐producible robots are used to perform large‐scale in situ sensing of outdoor environments. Herein, results from simulations of the system for an area coverage scenario and the first robot prototypes are reported. The physical robot developed can be rapidly assembled and then is able to perform a series of jumps using environmentally triggered latches.